Spatial analysis of the tuberculosis treatment dropout, Buenos Aires, Argentina - Herrero, María Belén; Arrossi, Silvina; Ramos, Silvina; Braga, Jose Ueleres (Revista de Saúde Pública, 2015)
Areas with higher proportion of the population without social security benefits (p = 0.007) and of households with unsatisfied basic needs had a higher risk of nonadherence (p = 0.032). In addition, the proportion of nonadherence was higher in areas with the highest proportion of households with no public transportation within 300 meters (p = 0.070)